Influence of variations in stiffness of cervical ligaments on C5-C6 segment. (August 2017) - Wang, Kuan; Deng, Zhen; Wang, Huihao; Li, Zhengyan; Zhan, Hongsheng; Niu, Wenxin
Abstract: The ligaments of the cervical spine each play a critical role in maintaining stability. Large variations in the mechanical behavior of each ligament have been reported, but it remains unclear how these variations influence cervical biomechanics. The objective of this study was to investigate the mechanical response of the cervical spine to variations in the properties of each cervical ligament. A finite element model of the C5-C6 spine was constructed with the average material properties. The stiffness of each ligament was then changed in turn by increasing or decreasing it per its designated maximum or minimum stiffness. The range of motion (ROM) and intradiscal pressure (IDP) were calculated and compared among the different models under pure moments. The results showed that the capsular ligament with the greatest stiffness caused a lower ROM in all anatomical planes. Varying the stiffness of the anterior longitudinal ligament had the greatest influence on ROM in extension, while the interspinous ligament was the most influential in flexion. During lateral bending or axial rotation, the capsular ligament with the minimum stiffness resulted in a higher IDP, while the capsular ligament with the maximum stiffness resulted in a lower IDP. Varying the capsular ligament stiffness had the greatest role on the C5-C6 ROM and therefore care must be taken to assign appropriate material properties. This study showed a less influence on the intervertebral disc with smaller ROM, especially when the ligaments were relaxed. This suggested that the control of the neck posture may be beneficial for patients with a degenerated cervical spine. Highlights: This study analyzed the influence of variations in stiffness of cervical ligaments. The stiffness of capsular ligament greatly affected the C5-C6 ROM. Less influence of ligaments affected on the intervertebral disc with smaller ROM. Care must be taken to assign appropriate material properties of capsular ligament in FE modeling. Control of the neck posture is beneficial for patients with degenerated cervical spines.